Effect of dsp mutations on the cell-to-cell transmission of CsgA in Myxococcus xanthus. - Li, S F (1993)
The dsp locus contains genes involved in the subunit synthesis and/or assembly of fibrils that radiate outward from the Myxococcus xanthus cell surface and attach to other cells. The csgA gene encodes an extracellular protein morphogen which is essential for fruiting body development. The question of whether fibrils are involved in the transmission of CsgA to adjacent cells was investigated in three ways. First, the dsp and csgA mutants were mixed in a ratio of 1:1 and allowed to develop; fruiting bodies containing spores derived from the csgA mutant were formed, suggesting efficient CsgA transfer. Second, the csgA mutation affected expression of many developmentally regulated genes differently from the way dsp affected their expression. Third, the expression of one developmentally regulated gene, which was partially expressed in csgA and dsp backgrounds, was almost completely inhibited in the presence of both mutations, suggesting that its promoter is regulated independently by two distinct stimuli, one that is csgA dependent and one that is dsp dependent. Together these results argue that fibrils are not necessary for cell-to-cell transmission or perception of CsgA, and their precise function remains unknown.